Proposal for the elaboration of a medical student code of ethics - Bazán, Ethel (1996)
The author and a group of students propose this document consisting of 38 articles aimed to give the elements for the elaboration of a code that guide the conduct of the students in relation to themselves, their teachers, colleagues, relatives and patients that participate in their formative period.